Safeguarding Village Neutrality: A Legal Analysis of the Prohibition on Village Heads Joining Political Parties Post-Constitutional Court Decision 76/PUU-XXI/2023 - Arif Putra Pratama Arif (Socio Legal and Islamic Law, 2024)
The prohibition of village heads from joining political parties under Constitutional Court Decision No. 76/PUU-XXI/2023 sparks debate regarding political rights within village autonomy. This research aims to analyze the alignment of the decision's legal considerations within the Indonesian legal system and identify implementation challenges stemming from the extensive authority of village heads. The research method used is socio-legal. The results show that the judges' considerations in Decision No. 76/PUU-XXI/2023 are aligned with the hierarchy of laws and regulations, positioning the village head as a government administrator mandatory to maintain neutrality for impartial public service. However, implementing this decision faces significant challenges because village heads hold centralized power (executive and budget management) and are products of political elections (Pilkades) often tied to local interests. Such vast authority is prone to misuse for practical political purposes through mass mobilization. Therefore, the effectiveness of this prohibition cannot rely solely on legal norms; it requires strengthening village leadership ethics and strict supervision to ensure village authority does not become an instrument for specific political parties.